Psychosocial risks of women workers in the public sector: the moderating role of job satisfaction on work absenteeism - Sánchez-Ollero, José Luis; Del-Cubo-Arroyo, Elisa (My University, 2017)
Transformation in the management of human resources in the public sector has led to new approaches to the organization of work within a setting characterised by a strict hierarchy and entrenched procedures. These changes are often understood in different ways and lead to individual and collective attitudinal responses that have an impact on job satisfaction and the experience of stress. Given the high percentage of women who work in the public sector and their traditional social role, we analysed their perceptions of and responses to psychosocial risk factors in relation to work absenteeism. Data collection and Methodology: Use CoPsoQISTAS21 questionnaire for psychosocial risk assessment (2014) and development of a structural equation model (PLS) on SmartPLS2.0 M3 program are used to estimate the psychosocial factors associated with absenteeism and the moderating role of job satisfaction with the aim of developing programs for the prevention of psychosocial risk among women working in the public sector. Results: The results show the submodel measure has crossloads> 0.7 in all indicators. AVE>0.5, composite reliability> 0.8 and Cronbach α > 0.7. The structural submodel shows R2> 0.1 and regression coefficients t-statistics> 2 confirming the four basic hypotheses. Conclusions: The psychosocial factors that influence the development of the new skills required by public sector reforms affect the level of stress experienced by women. In particular, these psychosocial factors influence respect and recognition received from superiors and colleagues, the support received at work both in general and in difficult situations, and the quality of leadership in planning, conflict resolution, and group communication.
Keywords: Mujeres - Trabajo; Public sector; Job satisfaction; Psychosocial risk; Gender; Absenteeism